ANALISIS PENGARUH NET PROFIT MARGIN, RETURN ON ASSETS, DEBT TO EQUITY RATIO, RETURN ON EQUITY DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Luluk Badriyah, 10.05.52.0079; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2014)
The Â objectiveÂ  ofÂ  theÂ  studyÂ  isÂ  toÂ  examineÂ  theÂ  effectÂ  ofNet Profit Margin (NPM), Return on Assets (ROA), Debt to Equity Ratio (DER), Return on Equity (ROE) and Current Ratio (CR)on Stock Prices. This study was taken because there are still differences between the research study with each other. This research was conducted using secondary data. Population in this research wasÂ  insuranceÂ  companyÂ  obtainedÂ  fromÂ  shareÂ  whichÂ  wasÂ  listedÂ  andÂ  âgoÂ  publicâÂ  in Indonesian Stock Exchage period 2010-2012. Sampling technique used was purposive sampling. There is 70 companies that can be analysed. This study is analyzed by using multiple regression. TheÂ  multipleÂ  regressionÂ  showsÂ  that Net Profit Margin significant positive effect on stock price, Return on Assets significant positive effect on stock price, Debt to Equity Ratio havenât significant positive effect on stock price, Return on Equity havenât significant negative effect on stock price, andÂ  Current Ratio havenât significant positive effect on stock price. Keywords: NPM, ROA, DER, ROE and Stock Price